2017
DOI: 10.1007/s40292-017-0243-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Biomarkers Release in Preadolescent Athletes After an High Intensity Exercise

Abstract: A short, high-intensity exercise caused an elevation of cardiac biomarkers in 62% of our subjects. The grade of training may influence the release of troponin and this increase is probably related to a temporary discrepancy between O2 delivery and consumption. Increases in natriuretic peptides levels are possibly expression of different adaptations to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
3
22
1
Order By: Relevance
“…In this regard, although our results support the assertion that the exercise-induced elevation of cTn might be independent of age, height, weight or experience, larger studies including wider age ranges are still needed to clarify this association. Weekly training frequency and volume at the time of the study, on the other hand, were not associated with ∆cTnT either, coinciding with previous reports [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this regard, although our results support the assertion that the exercise-induced elevation of cTn might be independent of age, height, weight or experience, larger studies including wider age ranges are still needed to clarify this association. Weekly training frequency and volume at the time of the study, on the other hand, were not associated with ∆cTnT either, coinciding with previous reports [31].…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, since HRmax was age-calculated, the baseline differences might be originate from the positive correlation found between basal cTnT and age. On the other hand, although previous research was inconclusive regarding the association between exercise HR and ∆cTnT [3][4][5]28,31], we found higher releases in participants achieving higher absolute heart rates. This finding adds to previous knowledge, supporting the idea that exercise load metrics, such as those recorded in training watches or smartphone apps, might be consulted to identify physiological elevations of cTnT related to exercise.…”
Section: Discussioncontrasting
confidence: 80%
“…Previous research in adult populations found that hs-cTnT release after exercise was associated with the peak and average heart rate during exercise [11]. However, our results coincide with recent studies that did not find such an association when investigating the phenomenon in younger participants [33,37]. The acute cardiovascular response to exercise in children is more variable than that in adults; this variability is probably a consequence of anatomical, physiological, and psychological changes that occur during growth and maturation [38].…”
Section: Discussionsupporting
confidence: 90%
“…It is difficult to discourage athletes from these practices, but they can be made aware, if there is evidence that such practices could affect their muscular functioning [3]. To explain this muscular damage, studies have been carried out on elite fighters and in healthy elite and amateur athletes who were evaluated after intensive exercise until muscular exhaustion, causing an elevation of cardiac biomarkers in 62% of the subjects like troponin, a possible indicator of heart damage, acute coronary syndrome, or even infarction [4][5][6][7][8][9][10][11]. Wrestlers were divided into groups, depending on their hydration levels, and it was concluded that the levels of inflammation and markers of muscle damage (creatine phosphokinase, CPK, lactate dehydrogenase, LDH, and aspartate transaminase, AST) obtained in their post-competition blood samples were different between both groups and higher in the forearm muscles of the dehydrated group.…”
Section: Introductionmentioning
confidence: 99%